The Association Between Social Determinants of Health and Postpartum Length of Stay During the COVID-19 Pandemic [A139]. (May 2022) - Lewis, Ayodele; Bunnell, Megan; Easter, Sarah Rae; McElrath, Thomas; Greenberg, James A.
Abstract : INTRODUCTION: To determine differences in cesarean postpartum length of stay (pLOS) before and during the COVID-19 pandemic as a function of social determinants of health. METHODS: Cesarean birth pLOS data between January 1 and June 30, 2020, were reviewed. Births after March 10, 2020, were considered pandemic births. Primary outcome was early discharge <5, 760 minutes (96 hours). Rates of early discharge were analyzed by social determinants of health, with socially vulnerable patients defined as Black or Hispanic, publicly insured, or non-English-speaking. We compared rates of early discharge before and during the pandemic overall and then among socially vulnerable patients using probit regression analysis. RESULTS: There were 1, 885 eligible deliveries: 694 before the start of the pandemic and 1, 171 after. Median pLOS pre-pandemic was 5, 696 (IQR, 4, 686–6, 060) minutes versus 4, 655 (IQR, 3, 897–5, 860) minutes during the pandemic. Of the eligible deliveries, 54% had early discharges pre-pandemic compared to 71% afterwards ( P <.01). Overall, we found these variables predictive of early discharge pLOS: socially vulnerable ( P <.01), payer type ( P <.01), English ability ( P <.01), and multiparity ( P <.01). Race as a variable alone was not found to be significantly predictive of early discharge. CONCLUSION: Socially vulnerable patients are more likely to leave the hospital earlier than their counterparts both before and during the COVID-19 pandemic. Our findings suggest that increased early discharges fall disproportionately on socially vulnerable patients. Further research is needed to determine whether these results are due to provider bias or patient driven.